2011
DOI: 10.1093/hmg/ddr453
|View full text |Cite
|
Sign up to set email alerts
|

Severe neuromuscular denervation of clinically relevant muscles in a mouse model of spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA), a motoneuron disease caused by a deficiency of the survival of motor neuron (SMN) protein, is characterized by motoneuron loss and muscle weakness. It remains unclear whether widespread loss of neuromuscular junctions (NMJs) is involved in SMA pathogenesis. We undertook a systematic examination of NMJ innervation patterns in >20 muscles in the SMNΔ7 SMA mouse model. We found that severe denervation (<50% fully innervated endplates) occurs selectively in many vulnerable axial musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
198
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(223 citation statements)
references
References 51 publications
21
198
0
Order By: Relevance
“…To determine whether dual treatment ameliorates the NMJ defects compared with MO E1v11 monotherapy, treatment groups were analyzed by immunofluorescent staining of the longissimus capitis muscle. This muscle was selected because prior studies have demonstrated that the longissimus capitis muscle is particularly sensitive and exhibits significant pathology with respect to NMJ maturation, denervation, and morphology in the SMNΔ7 mouse model (30). Both treatment groups resulted in visibly improved NMJ size and innervation compared with the untreated SMNΔ7 mouse ( Figure 5, A and B), as evidenced by the similar levels of fully innervated NMJs as well as the degree of partial and fully denervated end plates ( Figure 5C).…”
Section: E1v11mentioning
confidence: 99%
“…To determine whether dual treatment ameliorates the NMJ defects compared with MO E1v11 monotherapy, treatment groups were analyzed by immunofluorescent staining of the longissimus capitis muscle. This muscle was selected because prior studies have demonstrated that the longissimus capitis muscle is particularly sensitive and exhibits significant pathology with respect to NMJ maturation, denervation, and morphology in the SMNΔ7 mouse model (30). Both treatment groups resulted in visibly improved NMJ size and innervation compared with the untreated SMNΔ7 mouse ( Figure 5, A and B), as evidenced by the similar levels of fully innervated NMJs as well as the degree of partial and fully denervated end plates ( Figure 5C).…”
Section: E1v11mentioning
confidence: 99%
“…Some are highly affected, while others appear to be resistant. In many cases, these muscle-selective effects include how their NMJs react to these conditions (40,72,73). The mechanisms underlying these unique sensitivities remain elusive and are likely to be complex and condition specific.…”
Section: Figmentioning
confidence: 99%
“…This treatment concept has been validated in mouse models of SMA by several approaches including targeted transgenic expression of SMN1 in motor neurons, gene replacement with adeno-associated viruses, oligonucleotides that promote inclusion of exon 7, and histone deacetylase (HDAC) inhibitors that increase SMN expression (13)(14)(15). Additionally, SMA severity in human patients and SMA mouse models correlates with the number of SMN2 copies (16,17). Currently, there are about 18 therapeutic programs for SMA in various stages of preclinical and clinical development (18).…”
Section: Introductionmentioning
confidence: 99%